Feature : A shared journey of discovery. (30th August 2017) - Skuse, Benjamin
Abstract: Scientific collaborations often span the globe, but what happens when a potential colleague is someone much closer to home? Benjamin Skuse looks at the lives of researchers where science is a family affair